Analysis of Goverments Readliness for Regulatory Changes: Moderation Effect of Organizational Commitment - Nur Azlina; Ahrun Naza; julita julita (Fakultas Ekonomi, Universitas Bangka Belitung, 2020)
This research aims to examine the effect of human resources competency and communication on the readiness of local government in the implementation of PP number 12 of 2019 with organizational commitment as moderating variable. The population in this study is all regional units in Riau Province . The sample in this research amounted to 27 regional work units with 108 respondents. The method of determining the sample is by using the census sampling method, while the data processing method used by researchers is the multiple regression and moderate regression analysis and use SPSS version 25.0as the software for processing the data. The result of this research shows that the human resources competency and communication give a significant influence on the readiness of local government in the implementation of PP number 12 of 2019 . On organizational commitment as moderating variable have moderate relations on human resources competency and communication on the readiness of local government in the implementation of PP number 12 of 2019 . The results of the research can be added to the literature in the field of accounting knowledge and can be useful to present the readiness of local government in the implementation regulation. Keywords :Organizational commitment, Human Resources Competency, Communication, , and Readiness of PP Number 12 year 2019.